The very impatient caterpillar - Burach, Ross. (New York : Scholastic Press, 2019)
A caterpillar learns to be patient while trying to metamorphosize.
Booklist
Bulletin of the Center for Children's Books starre
School Library Journal
Booklist, January 2019
Bulletin of the Center for Children's Books starre, January 2019
Kirkus Review, October 2018
Keywords: Butterflies -- Juvenile fiction; Caterpillars -- Juvenile fiction; Metamorphosis -- Juvenile fiction; Patience -- Juvenile fiction; Butterflies -- Fiction; Caterpillars -- Fiction; Metamorphosis -- Fiction; Patience -- Fiction; Butterflies -- Fiction; Caterpillars -- Fiction; Metamorphosis -- Fiction; Patience -- Fiction; Picture books